Comparative genomic analyses of the cyanobacterium, Lyngbya aestuarii BL J, a powerful hydrogen producer. - Kothari, Ankita; Vaughn, Michael; Garcia-Pichel, Ferran (Frontiers in Microbiology, 2013)
The filamentous, non-heterocystous cyanobacterium Lyngbya aestuarii is an important contributor to marine intertidal microbial mats system worldwide. The recent isolate L. aestuarii BL J, is an unusually powerful hydrogen producer. Here we report a morphological, ultrastructural and genomic characterization of this strain to set the basis for future systems studies and applications of this organism. The filaments contain circa 17 μm wide trichomes, composed of stacked disk-like short cells (2 μm long), encased in a prominent, laminated exopolysaccharide sheath. Cellular division occurs by transversal centripetal growth of cross-walls, where several rounds of division proceed simultaneously. Filament division occurs by cell self-immolation of one or groups of cells (necridial cells) at the breakage point. Short, sheath-less, motile filaments (hormogonia) are also formed. Morphologically and phylogenetically L. aestuarii belongs to a clade of important cyanobacteria that include members of the marine Trichodesmiun and Hydrocoleum genera, as well as terrestrial Microcoleus vaginatus strains, and alkalyphilic strains of Arthrospira. A draft genome of strain BL J was compared to those of other cyanobacteria in order to ascertain some of its ecological constraints and biotechnological potential. The genome had an average GC content of 41.1 %. Of the 6.87 Mb sequenced, 6.44 Mb was present as large contigs (>10,000 bp). It contained 6515 putative protein-encoding genes, of which, 43 % encode proteins of known functional role, 26 % corresponded to proteins with domain or family assignments, 19.6 % encode conserved hypothetical proteins, and 11.3 % encode apparently unique hypothetical proteins. The strain’s genome reveals its adaptations to a life of exposure to intense solar radiation and desiccation. It likely employs the storage compounds, glycogen and cyanophycin but no polyhydroxyalkanoates, and can produce the osmolytes, trehalose and glycine betaine. According to i